Moneda antigua y vias Romanas en el noroeste de Hispania - Vila Franco, María Isabel, (Archaeopress Roman archaeology ;, 2016)
The main objective of this work was to obtain an overview of the Roman monetary circulation in Gallaecia following the road network that crossed this territory in Roman times.